Beef Grinding Business Development Strategy: Case Study in Kirimuka Market Business Unit, Depok, West Java - Nugroho Kesowo Murti; Stuart Hart; Mark G. Edwards; Encep Sopandi; Arief Zulkarnain; Tri Puji Hastutik (Journal of Social and Humanities, 2025)
This research focuses on the development of the beef milling agribusiness in the Kemiri Muka market, Depok, West Java, which plays a crucial role in meeting the beef consumption needs in West Depok. As a small-scale enterprise, the beef milling business presents opportunities for further development. The study aims to identify the internal and external conditions of the business and to formulate an effective development strategy using a SWOT analysis approach. Data was collected through various methods, including observation, interviews, questionnaires, literature review, and document analysis, using a purposive sampling technique. The study's findings propose several strategies: maximizing demand from regular customers, enhancing customer acquisition through effective marketing, expanding business networks, improving waste management to increase customer comfort, enlarging milling facilities, maintaining machinery quality, and upgrading human resources to sustain competitiveness. These strategies are essential for the growth and sustainability of the beef milling business in Kemiri Muka, Depok.